2014
DOI: 10.1017/s1047951113002072
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microemboli detection and differentiation during transcatheter closure of atrial septal defect in a paediatric population

Abstract: This is the first study to investigate the timing and composition of cerebral microemboli in a paediatric population during cardiac catheterisation. Microembolic signals were related to specific catheter manipulations but were not associated with fluoroscopic time or duration of procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…As we are not aware of published studies using the Sonara™ (Natus Medical Inc., Pleasanton, CA) TCD system for emboli detection in children with CHD undergoing cardiac catheterization, and performance of this system under these circumstances is unknown. We seemed to observe a larger burden of emboli in either clusters or curtains as compared to previous reports . Quantification of HITS close in time (embolic showers) is a major limitation of currently available TCD systems.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…As we are not aware of published studies using the Sonara™ (Natus Medical Inc., Pleasanton, CA) TCD system for emboli detection in children with CHD undergoing cardiac catheterization, and performance of this system under these circumstances is unknown. We seemed to observe a larger burden of emboli in either clusters or curtains as compared to previous reports . Quantification of HITS close in time (embolic showers) is a major limitation of currently available TCD systems.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite the broad range in underlying cardiac anatomy and physiology and procedures performed, pediatric studies have reported HITS occurring in “bursts” and clusters, often in association with a septal defect and/or right to left shunt . Maneuvers during catheterization for closure of atrial septal defects, namely, sheath placement, balloon sizing, and device placement, have been associated with HITS in children and young adults . Although not recorded for our study, other procedures in the catheterization laboratory, such as blood sampling and injection of drugs, fluids, and contrast agents, have also been reported to produce HITS .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Indeed, BS may enlarge the ASD by a laceration of the septum 26 and induces cerebral air microembols. 27 BS also increases the duration of the procedure and irradiation. Some authors moved towards and device selection without BS has already been safely performed.…”
Section: Discussionmentioning
confidence: 99%
“…BS was performed using the 'pullthrough' technique with the Meditech Equalizer balloon catheter (Boston Scientific, Natick, MA, USA). 13 The chosen occlusion balloon diameter (20,27,33, or 40 mm) was only slightly larger than the 2D-TEE ASD maximal diameter . The occlusion balloon was manually inflated into the left atrium filled with diluted contrast.…”
Section: Patients and Protocolsmentioning
confidence: 99%